The characteristics of spelling learning tools oriented to increasing Higher Order Thinking Skills in Elementary Schools - Main Sufanti; Markhamah Markhamah; Winarni Winarni (BAHASTRA, 2021)
The purpose of this study was to describe the characteristics of a spelling learning syllabus oriented towards improving Higher Order Thinking (Berpikir Tingkat Tinggi/BTT) skills in elementary schools; describe the characteristics of lesson plans for spelling learning oriented towards improving BTT abilities in elementary schools; describe the characteristics of the spelling learning LKPD oriented towards improving BTT abilities in elementary schools; and describe the characteristics of the spelling learning assessment oriented towards improving BTT abilities in elementary schools. This research is included in qualitative descriptive research. The data and data sources in this study were spelling learning tools oriented towards improving BTT skills in elementary schools. The data in this study were collected using documentation techniques, FGD, and questionnaires. The theory and source triangulation were used to validate the data. Interactive analysis techniques as data analysis techniques. The results showed that the spelling learning syllabus was oriented towards improving BTT abilities in elementary schools which had the characteristics of developing 21st century skills, focused-integrated, actual and contextual, flexible, and feasible; The lesson plan for spelling learning is oriented towards improving BTT abilities in elementary schools. It has the following characteristics: integrated, deep, and contemporary; Spelling learning LKPD oriented to improving BTT abilities in SD has the following characteristics: focus, activate students, and be interesting; Assessment of spelling learning to improve the BTT of elementary school students has the following characteristics: a contextual and holistic stimulus